(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines the creative activity of Kh.Tokhtaboev, the thematic scope of his works, and his artistic mastery in creating literary characters. Special attention is paid to the study of the artistic qualities of his works, their linguistic features, and issues of national identity. The writer’s contribution to the development of Uzbek children’s literature is also highlighted.